Análise do uso e ocupação do solo com ênfase no mapeamento da Floresta Urbana de Humaitá | Am - Ferreira, Sabrina Paiva (Brasil, 2021)
With the rise of technology, the fascination for urban life has initiated the migration of the resident population from rural to urban areas, leading to significant changes involving social, environmental and economic aspects. The urban growth is essential and inevitable, so it must be linked to measures that make it the best possible, attending primordial points for a healthy and pleasant stay in it. The knowledge and monitoring arising from the use of technology and sensing techniques are prime alternatives for a greater scope and understanding of the patterns of space organization, once their trends can be analyzed, with the purpose in generating spatial information that serve as a basis for planning a more balanced urban land use and occupation. The study was carried out in all the territory said to belong to the urban area of the city of Humaitá, allusive to the southern mesoregion of the State of Amazonas, at the junction of the Transamazonic highways BR230 and BR319, with latitude 07º 30' 22" South and longitude 63º 01' 15". It has a population of 57,195 inhabitants in its entire municipal area, and 69% living in the urban sphere, a value equivalent to 38,739 inhabitants, according to estimates made by the last census of the Brazilian Institute of Geography and Statistics (IBGE, 2021). In the construction of the maps, we chose to use the ArcGis 10.8 software, ArcMap extension, ArcGis Pro and Qgis. In analyzing the values plotted on the graph, it can be seen that the classes of dense vegetation and buildings are similar. This indicates a false correlation of an urban growth (2,7306919 km²) in conjunction with a sufficient forestation (2,8924524 km²). It is assessed on the urban forest map that vegetation is being pushed away to the edges of the urban territory as the city urbanizes, showing that the city does not have an efficient spatialization of this tree cover.